How do the financial markets respond to emerging economies' asset purchase program? Evidence from the Covid-19 crisis - K. P. Prabheesh; Sanjiv Kumar (Asian Development Bank Institute (ADBI), 2022)
This study examines the impacts of unconventional monetary policy on the exchange rate, stock market, and bond market during the COVID-19 economic crisis in an emerging economy. It focuses particularly on the asset purchase program conducted by the Central Bank of India. The Central Bank announced an asset purchase program four times during the pandemic. By applying the EGARCH methodology, this study finds that: (1) the asset purchase program effectively reduced the yield rate in the bond market and its volatility; (2) the first two announcements did not exert any impact on the financial market, but the third and fourth announcements helped to compress the yield and its volatility; (3) the program helped to restrain the exchange rate depreciation and volatility in the foreign exchange market; and (4) the impact of the announcements on stock returns, however, was weak.
Keywords: E44; E52; E58; E65; 330; unconventional monetary policy; bond market; exchange rate; stock market; EGARCH